Pride as a Catalyst for Student Engagement and Performance: The Roles of Psychological Capital and Teacher-Student Relationships - Qasim, Muhammad; Rizvi, Syed Tahir Hussain (Journal of Management and Research, 2024)
This study explores positive emotions in the context of students, focusing on the constructive impact of pride. The research aims to enhance the practical understanding of positive emotions centered around the broaden and build theory. Additionally, based on social learning theory, the article examines the moderating role of teacher-student relationship (TSR) to identify the association between psychological capital (PsyCap) and students' outcomes. To analyze the effects of pride on students' outcomes, PsyCap is introduced as a mediating mechanism, elucidating its influence on the relationship between pride and academic performance and engagement. Data from 328 students in diverse universities in Pakistan support our model, and the findings reveal a positive correlation between pride and academic performance and engagement. Moreover, TSR moderates the link between PsyCap and academic performance and student engagement. The positive association between PsyCap and academic performance and engagement strengthens when TSR is strong. This study contributes to the existing literature by highlighting the significance of positive emotions, particularly pride, in the academic context. The implications extend to theoretical and practical realms, providing insights into cultivating positive emotions and fostering a strong TSR. However, acknowledging study limitations, future research directions are required to address them.